Are Black and Latino adolescents being asked if they use electronic cigarettes and advised not to use them? Results from a community-based survey - Connolly, Margaret; Croft, Daniel; Ramírez-Palacios, Paula; Cai, Xueya; Hill, Beverly; Orfin, Rafael H.; Rivera, M. Patricia; Wilson, Karen M.; Li, Dongmei; McIntosh, Scott; Ossip, Deborah J.; Cupertino, Ana Paula; et al. (Frontiers in Public Health, 2023)
Objective: To explore if African American/Black and Hispanic/Latino adolescents are being asked if they use electronic cigarettes and advised not to use them. Methods: Adolescents with no vaping history, self-identifying as African American/Black and/or Hispanic/Latino, and able to read and speak English and/or Spanish were recruited through partner schools and community-based organizations. Participants completed a survey reporting sociodemographic characteristics, and if they were asked if they use electronic cigarettes and/or were advised not to use them by health professional. Results: Twelve percent of African American/Black and 5% of Hispanic/Latino participants reported not seeing a health professional in the year prior to enrollment. Of the participants who reported visiting a health professional, 50.8% reported being asked and advised about vaping. Over one quarter (28.4%) of participants were neither asked nor advised regarding vaping. Compared to English-speaking participants, Spanish-speaking participants were significantly less likely to be asked (45.2% vs 63.9%, p=0.009) and advised (40.3% vs 66.9%, p<0.001) about e-cigarette use. Moreover, compared to African American/Black participants, Hispanic/Latino participants were significantly less likely to be advised about e-cigarette use (52.9% vs 68.6%, p=0.018). Furthermore, compared to male participants, female participants were significantly less likely to be advised about vaping (51.3% vs 68.2%, p=0.003). Conclusion: Hispanic/Latino, Spanish-speaking, and female adolescents were significantly less likely to self-report being asked or advised about vaping compared to their Black/African American, English-speaking, and male counterparts. Future research is needed to improve health professional attention to asking about and advising against vaping among adolescents.